The effect of DMSO on ITS2 amplification in the molecular identification of Anopheles farauti Laveran (Diptera: Culicidae), from a colony established in the laboratory - Ign. Joko Suyono; Jesmandt Situmorang; R.C. Hidayat Soesilohadi; Rarastoeti Pratiwi (Perhimpunan Entomologi Indonesia, 2013)
Sibling species identification is very important in the understanding of malaria epidemiology. Morphological criteria are usually used in the identification of anopheline species, but this fails when sibling or cryptic species occur. Analysis by PCR-RFLP of rDNA ITS2 is currently the most reliable and sensitive method for distinguishing between members of the Anopheles punctulatus group. The objective of this study was to investigate the effect of DMSO concentration on ITS2 amplification of An. farauti from the colony maintained at BATAN Jakarta using PCR-RFLP based on the rDNA ITS2. The results showed that the addition of 6 % and 7 % DMSO produced ITS2 amplification products in the size 750 bp. DMSO could be used in PCR to relieve secondary structures when amplifying high GC templates. Molecular identification of An. farauti is found to be Anopheles farauti sensu stricto.